KEPASTIAN HUKUM KEPEMILIKAN HAK ATAS TANAH AKIBAT TERJADINYA SERTIFIKAT GANDA DI KANTOR PERTANAHAN/ATR KABUPATEN CIANJUR - Reta, Reta Dwi Murty (UNIB Press, 2024)
Article 19 paragraph (2) letter C of the Basic Agrarian Law (UUPA) emphasizes that certificates are a strong means of proof so that their owners are given legal certainty and legal protection. The approach method used by normative juridical aims to determine the factors causing the emergence of double certificates for land ownership at the Cianjur Regency Land Office/ATR, the impact that occurs if a double certificate is issued on the legal certainty of ownership of land rights, and the efforts made by the Land Office/ ATR Cianjur Regency in providing guarantees of legal certainty over land so that there are no double certificates. So it can be found that double certificates generally occur on land that is still empty or has not been developed and one of these is caused by the existence of a letter of evidence or acknowledgment of rights which is proven to contain untruths, falsehoods, or is no longer valid; One of the impacts of double certificates is that there is public unrest, especially for people seeking land who will always be filled with feelings of worry or fear that the land they are going to buy will turn out to be disputed land; and To minimize land disputes in dual certificates, one of the roles carried out by the Cianjur Regency National Land Agency (BPN) as a public servant is to review and manage data to resolve cases in the land sector. Keywords: Dual Certificate, Agrarian Law, National Land Agency (BPN).